The Basis for the Increase in Factor VIII Procoagulant Activity During Exercise - Kopitsky, Robert G; Switzer, Mary Ellen P; Williams, R Sanders; McKee, Patrick A (Thrombosis and Haemostasis, 1983)
We studied the effect of acute exercise on the ability of thrombin to activate plasma factor VIII (FVIII) activity in 20 healthy males. The subject showed an average exercise-related increase in FVIII activity of 54.5±8.2% over pre-exercise FVIII activity (p<0.001). When exposed to the same concentration of thrombin, post-exercise FVIII activity showed greater enhancement than pre-exercise FVIII activity: 157.1±12.8% increase in activity versus 117.3±9.9%, respectively (p<0.01). The degree of the potentiated thrombin effect in post-exercise samples relative to pre-exercise samples was linearly correlated with the degree of the exercise-related increase in FVIII activity. Taken together with our previous observations that the extent of thrombin enhancement of FVIII activity varies inversely with the mole ratio of FVIII/von Willebrand factor subunits to thrombin, these findings imply that release of FVIII does not occur during exercise, and that the exercise-related increase in FVIII activity results primarily, if not completely, from activation of already circulating but inactive FVIII.
Keywords: FVIII/vWF; Factor VIII/von Willebrand factor; Exercise and factor VIII activity increase; Thrombin and factor VIII